Law and Society in the Digital Era Regarding the Case of Scholarship Recipients from Education Fund Management Institutions from A Sociological Perspective - Hidayati Hidayati (International Journal of Social Service and Research, 2026)
Law and society are interconnected in the digital world. The viral case of a scholarship recipient from the Education Fund Management Institute whose nationalism declined due to insults to the state through social media, sparked a public movement responding to various opinions. This article aims to educate the public on the wise use of social media from a sociological perspective. The sociological research method uses a qualitative approach, employing a sociological perspective of law. The research results, according to social theory in global history, are manifested in the form of neoliberalism, with the intention of viewing society as individuals who behave as economic beings. This addresses the function of law in society to prevent conflicts of interest. If occur, the law becomes a tool used to resolve the consequences of individual violations that insult the state. According to the Law of the Republic of Indonesia, the Education Fund Management Institute Scholarship Agreement between the government and the people meets the requirements for the validity of the agreement as stipulated in Article 1320 of the Civil Code. This means that the agreement is legally binding for the parties bound by it. Violation of the Education Fund Management Institute Scholarship Agreement by failing to return to Indonesia to serve the national interest after completing studies can result in a civil lawsuit. A civil lawsuit based on breach of contract involves failure to fulfill obligations inherent in a valid agreement, namely the existence of a measurable agreement of rights and obligations (performance).